Sistem Informasi Manajemen sebagai Pemggerak Ekonomi Kreatif: Studi pada Startup dan Bisnis Digital Gen Z - Chairina Amaliah Hasibuan; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Digital transformation has changed the landscape of the creative economy in Indonesia, especially for Generation Z who utilize technology as the foundation of their business. This study aims to analyze the role of management information systems in driving the growth of startups and digital businesses managed by Gen Z through a literature review. The research method uses a library research approach by analyzing various literature sources in the form of scientific journals, books, research articles, and other relevant publications published in the period 2015-2024. The analysis technique uses content analysis to identify main themes, patterns, and conceptual relationships between variables. The results of the study show that management information systems make significant contributions in four main aspects: increasing business operational efficiency, optimizing data-based decision making, accelerating business scalability, and strengthening competitiveness in the digital market. These findings indicate that the integration of management information systems is a key factor in the success of the creative economy in the digital era, especially for young generations who have high technological literacy but require solid management structures for long-term business sustainability.